Protective role of MG53 against ischemia/reperfusion injury on multiple organs: A narrative review - Xu, Bowen; Wang, Chunxiao; Chen, Hongping; Zhang, Lihui; Gong, Lei; Zhong, Lin; Yang, Jun (Frontiers in Physiology, 2022)
Ischemia/reperfusion(I/R) injury is a common clinical problem, such as after coronary angioplasty, cardiopulmonary resuscitation, organ transplantation, which can lead to cell damage and death. Mitsugumin 53 (MG53), also known as Trim72, is a conservative member of TRIM family and is highly expressed in mouse skeletal and cardiac muscle, with very small amounts in humans. MG53 has been proved to be involved in the repair of cell membrane damage and has a protective effect on I/R injury in multiple oxygen-dependent organs, such as heart, brain, lung, kidney and liver. Recombinant human MG53 also plays a unique role in I/R, sepsis and other aspects, which is expected to provide new ideas for related treatment. This article briefly reviews the pathophysiology of I/R injury and the mechanism by which MG53 mitigates multi-organ I/R injury.